The role of public school principals and teachers in developing the social responsibility of students with learning disabilities: a joint perspective - Alsarayreh, Khaled Shaker Turki; Alramamneh, Abdellatif Khalaf; Al-Sabayleh, Obaid Abdelkarim; Al Remawi, Sameer Abdel Kareem Ahmad (Frontiers in Education, 2024)
IntroductionPublic school principals and teachers are crucial in shaping students with learning disabilities to become socially responsible individuals. Beyond academics, educators use adaptive teaching and leadership to instill values of empathy, cooperation, and civic duty in these students, ensuring they can contribute positively to their communities.AimThe present study aimed to identify the role of government school principals and teachers in developing the social responsibility of students with learning disabilities in the Kasbah of Salt from their viewpoint.MethodA descriptive analytical approach was used, where a random sample was taken from the principals and teachers of some of the Kasbah Al-Salt schools for the primary stage, and thus the sampling unit consisted of (106) principals and teachers, and the scale was sed, and it includes (27) items distributed on three dimensions of social responsibility (education, preservation Environment, community service).ResultsAccording to the findings of the study, the degree of social responsibility among students who have learning difficulties is comparable to the average level. However, the study also discovered that there are disparities in the level of social responsibility due to the gender variable, and these differences are in favor of males. In addition, there were no differences that could be considered statistically significant between the levels of social responsibility and the educational level variable.Scientific noveltyThe study’s novelty lies in its exploration of educators’ views on fostering social responsibility in students with learning disabilities in the specific context of the Kasbah of Salt. The research uses a descriptive analytical method, focuses on primary schools in Kasbah Al-Salt, employs the structured Melhem (2018) scale for evaluation, and reveals gender as a significant factor in social responsibility, while educational level is not.